2011
DOI: 10.1002/cbic.201100093
|View full text |Cite
|
Sign up to set email alerts
|

Gene Regulation System with an Artificial RNA Switch Operating in Human Cells

Abstract: Controlling gene expression: An artificial gene regulation system operating at the transcriptional level in human cells and based on allosteric control of an RNA–protein interaction with the aid of a small ligand has been constructed. This system could be regarded as an artificial RNA switch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…11,18 The fluorescence increase in TMR-Tat signal as a function of the concentration of RNAs was fitted assuming an equilibrium of a simple 1:1 binding reaction as follows:…”
Section: Assay For Interaction Between Tat Peptide and Aptamer-tars mentioning
confidence: 99%
“…11,18 The fluorescence increase in TMR-Tat signal as a function of the concentration of RNAs was fitted assuming an equilibrium of a simple 1:1 binding reaction as follows:…”
Section: Assay For Interaction Between Tat Peptide and Aptamer-tars mentioning
confidence: 99%
“…[10,21] The fluorescence increase or decrease of TMR-Tat as a function of the concentration of aptamer-TARs, assuming equilibrium of a simple 1:1 binding reaction, was fitted by using Equation (1), where F is the fluorescence signal of TMR-Tat at each concentration of aptamer-TARs, F initial is the initial fluorescence signal of TMR-Tat without aptamer-TAR, F final is the fluorescence signal when all TMR-Tat bound to aptamer-TAR, [Tat] is the total TMR-Tat concentration, and [apTAR] is the concentration of aptamer-TAR.…”
Section: Evaluation Of Association Constantsmentioning
confidence: 97%
“…The allosteric suppression was also confirmed in vitro using a Tat-derived peptide labeled with a fluorophore. [10] This suggested that theophylline binding could be detected by a fluorometric signal resulting from allosteric control of an RNA-peptide interaction. Further, as the molecular recognition and signaling domains are separated, the strategy should enable construction of a universal sensing system.…”
mentioning
confidence: 98%
See 2 more Smart Citations